Au‐nanoparticle‐decorated SnO2 nanorod sensor with enhanced xylene‐sensing performance. Issue 3 (17th November 2017) - Feng, Caihui; Teng, Fei; Xu, Yang; Zhang, Yajun; Fan, Tiehu; Lin, Tingting
Abstract: In this work, pure and Au‐nanoparticle‐decorated SnO2 nanorods were prepared via a one‐step hydrothermal method combined with a facile deposition process, and then characterized by X‐ray diffraction, scanning electron microscopy, transmission electron microscopy, high‐resolution transmission electron microscopy, and X‐ray photoelectron spectroscopy. The xylene‐sensing performance of the nanorods was also investigated. The results show that Au nanoparticles with an average diameter of 4‐6 nm were immobilized on the surface of rutile SnO2 nanorods. As the amount of Au increased, the surface‐adsorbed oxygen species gradually increased. The 12 mol% Au‐SnO2 nanorods exhibited the highest response to 50 ppm xylene, a lower operating temperature (279 to 255°C), favorable selectivity, and fast response‐recovery speed (3 and 4 seconds, respectively). These properties made the fabricated nanorods good candidates for xylene detection. The possible mechanism for the enhanced xylene‐sensing performance is discussed.